ALUMNI Indicator as a Criterion for Evaluating the Quality of Academic Institutions - Sando, Snežana; Ferenčak, Miroslav (International Journal of Industrial Engineering and Management, 2012)
This paper presents the model for ranking the quality of academic institutions, based on combination of academic and non – academic criteria. Each of the criteria consists of several indicators which are given certain relevance. The authors focused especially on the value of the ALUMNI indicator, which are given a total of 25% of the gravity factor. The use of this model will allow the forming of adequate methodology for the national ranking of the academic institutions. Article history: Received (17 April 2012); Revised (4 June 2012); Accepted (12 June 2012)